2009
DOI: 10.1002/andp.200910380
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance in dilute p-Si/SiGe in parallel and tilted magnetic fields

Abstract: We report the results of an experimental study of the magnetoresistance ρxx and ρxy in two samples of p-Si/SiGe with low carrier concentrations p=8.2×10 10 cm −2 and p=2×10 11 cm −2 . The research was performed in the temperature range of 0.3-2 K and in the magnetic fields of up to 18 T, parallel or tilted with respect to the two-dimensional (2D) channel plane. The large in-plane magnetoresistance can be explained by the influence of the in-plane magnetic field on the orbital motion of the charge carriers in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…While decent results were obtained on Ge:Mn ͑Ref. 4͒ and Si/SiGe, 5 it was found that that setup was suitable for short term ͑about 30-60 min long͒ experiments only. During longtime experiments the triggering cycle sometimes failed, and the added nanovoltmeter performed incorrect measurements.…”
mentioning
confidence: 76%
“…While decent results were obtained on Ge:Mn ͑Ref. 4͒ and Si/SiGe, 5 it was found that that setup was suitable for short term ͑about 30-60 min long͒ experiments only. During longtime experiments the triggering cycle sometimes failed, and the added nanovoltmeter performed incorrect measurements.…”
mentioning
confidence: 76%